2020
DOI: 10.1002/qj.3892
|View full text |Cite
|
Sign up to set email alerts
|

Representation of the Scandinavia–Greenland pattern and its relationship with the polar vortex in S2S forecast models

Abstract: The strength of the stratospheric polar vortex is a key contributor to subseasonal prediction during boreal winter. Anomalously weak polar vortex events can be induced by enhanced vertically propagating Rossby waves from the troposphere, driven by blocking and wave breaking. Here, we analyse a tropospheric pattern-the Scandinavia-Greenland (S-G) pattern-associated with both processes. The S-G pattern is defined as the second empirical orthogonal function (EOF) of mean sea-level pressure in the northeast Atlant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…Analogous results seem to hold at shorter time scales, e.g. Lee et al ( 2020a ); Lehtonen and Karpechko ( 2016 ); Domeisen et al ( 2020b ).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Analogous results seem to hold at shorter time scales, e.g. Lee et al ( 2020a ); Lehtonen and Karpechko ( 2016 ); Domeisen et al ( 2020b ).…”
Section: Discussionmentioning
confidence: 60%
“…This bias is consistent with findings by Garfinkel et al ( 2019 ), who revealed a recent weakening of the ENSO–SPV teleconnection that is not captured by climate models. The weakening is thought to be induced by the increasing importance of the Eurasian eddy heat flux (Garfinkel et al 2019 ; Cohen et al 2019 ; Peings 2019 ; White et al 2018 ; Lee et al 2020a ; Domeisen et al 2020b ). We also report that a weak connection of the QBO with the SPV in the C3S multi-model may provide some vortex predictability, but a comparison with the strong observed connection confirms issues in the modelling of the Holton–Tan mechanism (Garfinkel et al 2018 ; Butler et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We first examine and compare biases in the NH eddy heat fluxes among the subseasonal forecast systems. The representation of heat fluxes in the Scandinavian/Siberian region has been shown in previous work using S2S models to be deficient (Garfinkel et al, 2019;Lee et al, 2020), and thus we show the evolution of the biases in this region in Figure 5d. In most models the week-1 Scandinavian/Siberian heat flux biases are small in magnitude, especially for the high-top models.…”
Section: Northern Hemisphere Polar Vortex Variabilitymentioning
confidence: 59%
“…The timescale of weeks for the predictability of sudden warmings is limited by the predictability of weather patterns in the troposphere which might trigger SSW events (e.g. Mukougawa et al, 2005;Taguchi, 2016;Garfinkel and Schwarz, 2017;Jucker and Reichler, 2018;Lee et al, 2020a). However, if we add this timescale to the timescale of a month or more for the persistence of lower-stratospheric anomalies and their surface effects (e.g.…”
Section: The Stratosphere and Monthly Predictionmentioning
confidence: 99%